Targeting P-selectin and interleukin-1b in mice with sickle cell disease: effects on vaso-occlusion, liver injury and organ iron deposition - Gotardo, Erica M.F.; Torres, Lidiane S.; Zaidan, Bruna Cunha; Gushiken, Lucas F.S.; Brito, Pamela L.; Leonardo, Flavia C.; Pellizzon, Claudia H. [UNESP]; Millholland, John; Agoulnik, Sergei; Kovarik, Jiri; Costa, Fernando F.; Conran, Nicola (Ferrata Storti Foundation (Haematologica), 2025)
Continuous vaso-occlusive and inflammatory processes cause extensive end-organ damage in adults with sickle cell disease (SCD), and there is little evidence that long-term hydroxyurea therapy prevents this. In initial trials, P-selectin blockade with crizanlizumab reduced SCD vaso-occlusive crisis frequency, and interleukin (IL)-1b inhibition in SCD patients, using canakinumab, lowered inflammatory markers. We used murine SCD models to examine the effects of acute and chronic blockade of P-selectin and of IL-1b on vaso-occlusive events, their inflammatory profile and organ health. Both approaches improved impaired cutaneous microvascular perfusion in SCD mice by reducing TNF-α-induced vaso-occlusion. Acute P-selectin blockade markedly reduced TNF-α-induced neutrophil-platelet aggregate formation in SCD mice, and decreased leukocyte-rolling movements in the microvasculature, while acute IL-1b inhibition attenuated microvascular leukocyte adhesion. Six weeks of IL-1b-blocking immunotherapy improved the inflammatory profile of SCD mice, considerably reduced hepatic fibrosis and provided some relief from lung injury. In contrast, although P-selectin blockade reduced glomerular congestion, no significant benefit to overall organ pathology was observed. Unexpectedly, while combining the two immunotherapies reduced microvascular occlusion, their prolonged use caused acute liver injury. Notably, inhibition of IL-1b, but not of P-selectin, remarkably decreased hemosiderosis, in association with reduced tissue macrophage infiltration and the correction of biomarkers of dysregulated iron turnover. Our findings suggest that the attenuation of inflammation, as well as of vaso-occlusive processes, may be crucial for mitigating organ damage in SCD. Future trials should explore the ability of cytokine blockade to prevent multi-organ damage in patients with SCD, beyond evaluating vaso-occlusive crisis frequency.